Synthesis of arithmetic circuits : FPGA, ASIC and embedded systems - Deschamps, Jean-Pierre, 1945- (John Wiley, 2006)
A new approach to the study of arithmetic circuitsIn Synthesis of Arithmetic Circuits: FPGA, ASIC and Embedded Systems, the authors take a novel approach of presenting methods and examples for the synthesis of arithmetic circuits that better reflects the needs of today's computer system designers and engineers. Unlike other publications that limit discussion to arithmetic units for general-purpose computers, this text features a practical focus on embedded systems. Following an introductory chapter, the publication is divided into two parts. The first part, Mathematical Aspects and Algorithms.